Antimicrobial Resistance among Escherichia Coli Causing UTIs in Women - Hawraa Wahab Aziz; Israa Adnan Ibraheam; Hawraa Sabah Almusawi; Zeana AL Hindi; Tsahel H. Al-Dulaimi (Journal of Global Pharma Technology, 2017)
Urinary tract infections (UTIs) are common bacterial infections, particularly in women. E. coli is one of the most frequently isolated bacteria in (UTIs), , it also caused of childhood diarrhea, severe anemia, ,kidney failure, pneumonia, sinusitis and endocarditis. The current study tried to detecting Antimicrobial Resistance Among Escherichia coli Causing UTIs in women. Of the total 48 isolates of Escherichia coli, very high rates of resistance was seen with Ticarcillin 48 (100%), Piperacillin48 (100%), Aztreonam 46 (95.8%), Cefepime and 44 (91.6%) Ceftazidime 44 (91.6%) . High rates of sensitive was seen with Imipenem 48 (100%), Meropenem 48 (100%), Amikacin 46(95.8%) , Gentamicin 32 (66.6%) , Piperacillin32(66.6%), Tobramycin 28 (58.3%) and ciprofloxacin 26(54.1%) , while of Minocycline 8 (16.6 %) has intermediate susceptibility to antibiotics study .According to the last results the most effective antibiotics were Meropenem , Imipenem and Amikacin so they are considered the best drugs used for treatment of UTIs which caused by Escherichia coli. Keywords: Antibiotics, E. coli, Urinary Tract Infection, Vitek, Antimicrobial Susstebility.